Interactions between heavy metals and glucosinolates as defense mechanisms in Thlaspi caerulescens - Asad, Saeed Ahmad (2011)
Hyperaccumulator plant species grow in metalliferous soils and accumulate exceedingly high concentrations of metals. They are increasingly studied because of their potential for cleaning up land contaminated with heavy metals, but another aspect of study relates to the reason for hyperaccumulation. The most accepted hypothesis over the last few decades is the ‘elemental defence’ hypothesis, which states that high levels of metals defend the plant against herbivores. Whilst some of the literature is contradictory, some is supportive. An added complication is that many hyperaccumulators belong to the Brassicaceae and produce glucosinolates as organic defences against herbivory. The question to be answered is whether metals or glucosinolates act as the primary defence in these plants and the most recent suggestion is the ‘joint effects’ hypothesis, which states that both classes of chemical work together to benefit the plant and protect it from herbivores.